The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/micr.20835
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of color duplex sonography in preoperative assessment of anterolateral thigh flap

Abstract: The anterolateral thigh (ALT) flap has become a workhorse in reconstructive surgery of the head and neck region and the extremities. However, its inconsistent vascular anatomy and frequent intramuscular course of perforators often cause difficulties during the dissection of this versatile flap. Hence, reliable preoperative perforator mapping and identification of vascular anomalies may render the raising of the flap easier and safer. The aim of this study was to evaluate the use of Color Duplex sonography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 25 publications
1
47
0
4
Order By: Relevance
“…Data obtained in our study confirms that CDU is highly sensitive, over 93%, when used for preoperative perforator mapping. These findings correlate well with other published data [26,27], showing the high level of reproducibility among various studies.…”
Section: Discussionsupporting
confidence: 92%
“…Data obtained in our study confirms that CDU is highly sensitive, over 93%, when used for preoperative perforator mapping. These findings correlate well with other published data [26,27], showing the high level of reproducibility among various studies.…”
Section: Discussionsupporting
confidence: 92%
“…Literature on the validity of the Doppler for detecting perforators has shown variable results. Giunta et al and Ensat et al found positive predictive value rates of 52% and 69%, respectively [12,13]. Two other studies reported higher positive predictive value rates varying from 82 to 94% [14,16].…”
Section: Discussionmentioning
confidence: 88%
“…So far the Doppler device has only been studied for its validity, which means that a positive signal indicates the presence of a perforator [10][11][12][13][14][15][16][17]. The presented validity properties of the Doppler device differ considerably across studies [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…To speed up raising the flap and facilitate planning of the initial skin incision with which to expose the perforator, techniques such as computed tomography (CT) or magnetic resonance (MR) angiography (Habib A, et al The role of preoperative perforator mapping using CT angiography compared with conventional Doppler in the successful harvest of antero-lateral thigh flaps: a comparative prospective study. Paper presented at the annual meeting of the British Association of Oral and Maxillofacial Surgeons, 2011), 22,23 near infrared spectroscopy 24 or colourcoded Duplex sonography 25 have been suggested. These methods have been proved to detect perforators in at least 95% of cases.…”
Section: Preoperative Planningmentioning
confidence: 99%